Does the board's human capital, social capital and participation affect co-operative performance? the case of Program Desa Lestari - Buang, Mokhtaruddin; Abu Samah, Asnarulkhadi; Rosnon, Mohd Roslan; Burhan, Nik Ahmad Sufian (Universidad Complutense de Madrid, 2023)
The Malaysian government has implemented a number of community development programmes, and this effort has been continued with the introduction of Program Desa Lestari. Program Desa Lestari is the government's most recent community development initiative, emphasising co-operative as a community development strategy. Given the co-operatives' position as the driving force behind this initiative, it is important that the current research examine cooperative performance, which is reliant on the board's ability to effectively fulfil their roles. Several board-related factors have been postulated, and this study has focused on the provision roles of board members' resources derived from human and social capital, with the inclusion of a mediation function of board participation. This study adopts a quantitative research approach using a correlation research design. Applying a proportional stratified sampling method, data were gathered from questionnaires distributed online and postal. The data from 226 eligible responses from 38 cooperatives were then analysed. A Partial Least Squares Structural Equation Modeling (PLS-SEM) approach was used to analyse the data. Overall, co-operative performance in Program Desa Lestari was found to be moderate, with most cooperatives (ƒ = 21) performing at an average to a very satisfactory level (51 and above). Interestingly, despite respondents' high levels of human capital and social capital in the current study, the findings revealed that these factors had no impact on co-operative performance, which in turn influences the mediating role of board participation. This study, however, serves as prospective research as it is the first to integrate the resource dependence theory and participation theory in investigating the effectiveness of board members on co-operatives performance especially in the context of Malaysia.